Upper Extremity Splint ApplicationMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's Method - Jonathan D. Grabau, MD; Hannah T. Hoopes, MD; Christine Ho, MD (Journal of the Pediatric Orthopaedic Society of North America, 2025)
The purpose of this chapter is to provide a basic instructional reference for upper extremity splint application in the context of pediatric orthopaedic trauma. In addition to reviewing the steps necessary for successful splint application, this chapter will also discuss common pitfalls to avoid in order to optimize outcomes and prevent complications during and after splint immobilization for upper extremity injuries. Embedded throughout the chapter are figures and videos that highlight how to apply various splints to the upper extremity based on the injury location and the immobilization required for different clinical situations. Previous studies have indicated that many practitioners caring for pediatric trauma patients lack the proper training to apply splints safely and effectively. This chapter and its accompanying media should ideally serve as a primer for medical trainees, including orthopaedic residents, fellows, advanced practice providers, and other medical professionals learning to treat pediatric patients in clinical and emergency department settings. Generally, upper extremity splints are used as a method of temporary immobilization while awaiting definitive management, which may involve conversion to a cast once the swelling has resolved or following surgical intervention. Key Concepts: (1) Splints should be considered for pediatric patients with upper extremity injuries when associated soft tissue injuries or anticipated swelling prevent the use of a cast. (2) Similar to casting, upper extremity splints should immobilize the injured area while minimizing the immobilization of uninjured joints. This approach allows for a continued range of motion and helps prevent iatrogenic stiffness. (3) Successful splint application depends on the proper use of cast padding and plaster to effectively immobilize injuries and prevent iatrogenic soft tissue complications like wounds or skin ulceration.